Multilevel Approaches and the Firm-Agglomeration Ambiguity in Economic Growth Studies - Frank G. van Oort; Martijn J. Burger; Joris Knoben; Otto Raspe (Tinbergen Institute, 2012)
Empirical studies in spatial economics have shown that agglomeration economies may be a source of the uneven distribution of economic activities and economic growth across cities and regions. Both localization and urbanization economies are hypothesized to foster agglomeration and growth, but recent meta-analyses of this burgeoning body of empirical research show that the results are ambiguous. Recent overviews show that this ambiguity is fuelled by measurement issues and heterogeneity in terms of scale of time and space, aggregation, growth definitions, and the functional form of the models applied. Alternatively, in this paper, we argue that ambiguity may be due to a lack of research on firm-level performance in agglomerations. This research is necessary because the theories that underlie agglomeration economies are microeconomic in nature. Hierarchical or multilevel modeling, which allows micro levels and macro levels to be modeled simultaneously, is becoming an increasingly common practice in the social sciences. As illustrated by detailed Dutch data on firm-level productivity, employment growth and firm survival, we argue that these approaches are also suitable for reducing the ambiguity surrounding the agglomeration-firm performance relationship and for addressing spatial, sectoral and cross-level heterogeneity.
urn:NBN:nl:ui:15-1765/31776
Keywords: C21; O18; R1; 330; agglomeration economies; micro-macro link; multilevel analysis; productivity; Produktivität; Räumliche Verteilung; Agglomerationseffekt; Niederlande